Beyond the Stages of Change: Spiritual and Managerial Integration in Faith-Based Behavioral Transformation - Ahmad Saefulloh; Abdul Haris; Syafrul Nalus; Zainap Hartati; Piter Joko Nugroho (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to examine how Islamic education management integrates spirituality, local wisdom, and institutional culture to facilitate a transformative recovery process in a faith-based rehabilitation setting. This study employed a qualitative design with a transcendental phenomenological approach. Data were collected through in-depth interviews, observations, and document analysis. Data were analyzed using NVivo and mapped onto the Transtheoretical Model of Change to capture the gradual dynamics of behavioral transformation. The results indicate that recovery occurs gradually and non-linearly. In the initial stage, local wisdom reflected in Islamic boarding school traditions and communal spiritual practices serves as a non-coercive mechanism for psychological and spiritual stabilization. As participants progress, an institutional culture characterized by relational security, moral role models, and collective discipline supports readiness and active engagement. In the later stages, recovery is sustained through identity reconstruction, spiritual continuity, and long-term relational attachments within the institutional environment. This study contributes by integrating the Transtheoretical Model of Change into Islamic education management and demonstrating how spirituality and local wisdom serve as managerial resources for sustainable recovery. These findings provide theoretical and practical implications in the development of a culturally based, non-punitive, and spiritually grounded educational rehabilitation model.